Carry trades and monetary conditions - Andrea Falconio (European Central Bank (ECB), 2016)
This paper investigates the relation between monetary conditions and the excess returns arising from an investment strategy that con- sists of borrowing low-interest rate currencies and investing in currencies with high interest rates, so-called "carry trade". The results indicate that carry trade average excess return, Sharpe ratio and 5% quantile differ substantially across expansive and restrictive conventional mone- tary policy before the onset of the recent financial crisis. By contrast, the considered parameters are not affected by unconventional monetary policy during the financial crisis.
Keywords: F31; G15; E52; 330; carry trade; monetary conditions; volatility